2020
DOI: 10.1186/s12888-020-02751-5
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive performance in children and adolescents at high-risk for obsessive-compulsive disorder

Abstract: Background: Cognitive performance has been studied in adults with obsessive-compulsive symptoms (OCS) and in adult relatives of patients with obsessive-compulsive disorder (OCD) Meanwhile, few studies have been conducted with children under the same conditions. This study compared the neurocognitive domains previously associated with dysfunction in OCD, especially visuoconstructive ability, visuospatial memory, executive functions, and intelligence, in children and adolescents at high risk (HR) for OCD (n = 18… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 84 publications
(108 reference statements)
0
5
0
Order By: Relevance
“…Despite not fulfilling the diagnostic criteria and having relatively low levels of symptom severity, subclinical OCS have been associated with psychiatric comorbidities and impaired functioning in the literature ( 5 , 41 , 42 ). A recent neuropsychological study of children and adolescents with OCS that were first-degree relatives of an individual with OCD identified impairments in spatial working memory and a trend in significance for impairment in motor and processing speed ( 43 ). Here we found that the presence of OCS may be directly associated with right thalamic volumes change, and the thalamus is a key element of the cortico-striato-thalamo-cortical (CSTC) circuits that are implicated in the pathophysiology of OCD ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite not fulfilling the diagnostic criteria and having relatively low levels of symptom severity, subclinical OCS have been associated with psychiatric comorbidities and impaired functioning in the literature ( 5 , 41 , 42 ). A recent neuropsychological study of children and adolescents with OCS that were first-degree relatives of an individual with OCD identified impairments in spatial working memory and a trend in significance for impairment in motor and processing speed ( 43 ). Here we found that the presence of OCS may be directly associated with right thalamic volumes change, and the thalamus is a key element of the cortico-striato-thalamo-cortical (CSTC) circuits that are implicated in the pathophysiology of OCD ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…5 Research literature indicates that individuals with OCD have impairment of some cognitive functions such as executive functions, information processing speed, attention, and memory. 6 Evidence suggests that patients with OCD function differently in some memory-related tasks, especially, those of retrospective and prospective memory. 7 , 8 Vafa et al studied retrospective, prospective, and short-term memory in patients with OCD and non-patients.…”
Section: Ethical Publication Statementmentioning
confidence: 99%
“…Impaired decision making has not only been detected in participants with OCD, but it has been suggested that it can be a core feature of OCD (da Rocha et al, 2011). There is also evidence toward neuropsychological deficits in pediatric OCD populations considering visual memory and spatial working memory (Andrés et al, 2007;Bernardes et al, 2020). While some people with OCD complain about having difficulties concentrating, there is no demonstrated neurobiological overlap between OCD and ADHD.…”
Section: Psychological Distress Mental Healthmentioning
confidence: 99%